A Cross-Sectional Multicenter Study of Multidimensional Body Image in Adolescents and Adults with Gender Dysphoria Before and After Transition-Related Medical Interventions - Becker, Inga; Auer, Matthias; Barkmann, Claus; Fuss, Johannes; Moeller, Birgit; Nieder, Timo O.; Fahrenkrug, Saskia; Hildebrandt, Thomas; Richter-Appelt, Hertha (Archives of Sexual Behavior, 2018)
Persistent feelings of gender dysphoria (GD) are accompanied by distress and body dissatisfaction in most clinically referred adolescents and adults. Transition-related medical interventions (e.g., puberty suppression, hormones, or surgery) may alleviate body dissatisfaction. The aim of the present cross-sectional study was to compare multidimensional body image across clinically referred adolescents and adults undergoing different transition-related medical interventions. Two clinical samples of adolescents (n = 82) and adults (n = 120) referred to specialized departments of four different transgender health services in Germany participated in the study. In total, 202 individuals from the female-to-male (FtM individuals) and male-to-female (MtF individuals) spectrum aged 14-74 years were included at different stages of their transition. Four scales assessing multidimensional aspects of body image (measured by the Body Image Assessment Questionnaire, FBeK) were compared across three groups: sample, gender, and medical interventions (while controlling for age and treatment duration). The results indicated less favorable body image scores compared with the norm in both adolescents and adults with GD. Individuals who had undergone transition-related medical interventions presented a significantly better body image on two of the four scales. Differences according to gender and age were also present. These findings suggest that medical interventions, especially gender-affirming hormones and surgery, are generally beneficial to the body image in individuals with GD. However, not all of the less favorable outcomes in multidimensional body image were positively influenced by the treatment conditions and may thus benefit from additional integrative counseling before and during transition.
EVALuna2:210261